Quand la réflexivité s'invite dans un dispositif de simulation - Xavier Léon; Laurent Van Belleghem
Training the engineers and managers of tomorrow means preparing them to act in the world of labor and corporations as it will be ; knowing how to cooperate facing the complex challenges (ecology, geopolitics, health, etc.) of our societies. Based on a business game played in an engineering school, this article exposes a comprehensive analysis of a game session and draws lessons from it, both operational and scientific. How does the meccanism, which allows simulating an experience making reflexivity possible, contribute to developing a professional posture - competent, relevant and ethical - in the making?